Temperature impacts community structure and function of phototrophic Chloroflexi and Cyanobacteria in two alkaline hot springs in Yellowstone National Park. Issue 5 (26th July 2020) - Bennett, Annastacia C.; Murugapiran, Senthil K.; Hamilton, Trinity L.
Summary: Photosynthetic bacteria are abundant in alkaline, terrestrial hot springs and there is a long history of research on phototrophs in Yellowstone National Park (YNP). Hot springs provide a framework to examine the ecophysiology of phototrophs in situ because they provide natural gradients of geochemistry, pH and temperature. Phototrophs within the Cyanobacteria and Chloroflexi groups are frequently observed in alkaline hot springs. Decades of research has determined that temperature constrains Cyanobacteria in alkaline hot springs, but factors that constrain the distribution of phototrophic Chloroflexi remain unresolved. Using a combination of 16S rRNA gene sequencing and photoassimilation microcosms, we tested the hypothesis that temperature would constrain the activity and composition of phototrophic Cyanobacteria and Chloroflexi. We expected diversity and rates of photoassimilation to decrease with increasing temperature. We report 16S rRNA amplicon sequencing along with carbon isotope signatures and photoassimilation from 45 to 72°C in two alkaline hot springs. We find that Roseiflexus, Chloroflexus (Chloroflexi) and Leptococcus (Cyanobacteria) operational taxonomic units (OTUs) have distinct distributions with temperature. This distribution suggests that, like phototrophic Cyanobacteria, temperature selects for specific phototrophic Chloroflexi taxa. The richness of phototrophic Cyanobacteria decreased with increasing temperature along with a decrease in oxygenic photosynthesis, whereas Chloroflexi richness and rates of anoxygenic photosynthesis did not decrease with increasing temperature, even at temperatures approaching the upper limit of photosynthesis ( 72–73°C). Our carbon isotopic data suggest an increasing prevalence of the 3‐hydroxypropionate pathway with decreasing temperature coincident with photoautotrophic Chloroflexi. Together these results indicate temperature plays a role in defining the niche space of phototrophic Chloroflexi (as has been observed for Cyanobacteria), but other factors such as morphology, geochemistry, or metabolic diversity of Chloroflexi, in addition to temperature, could determine the niche space of this highly versatile group.